BS EN IEC 55016-1-4. Specification for radio disturbance and immunity measuring apparatus and methods. Radio disturbance and immunity measuring apparatus. Antennas and test sites for radiated disturbance measurements (13th May 2022) - British Standards Institution
No abstract available